IMPLEMENTASI INTERNET OF THINGS PADA SMARTWATCH DALAM MENDUKUNG AKTIVITAS KEHIDUPAN SEHARI-HARI - Kelvin Fernando; Adrianus Bagas P.Y.U; Dorie P. Kesuma (Jurnal Riset Teknik Komputer, 2026)
The current development of modern wearable technology has brought forth various crucial innovations, one of which is the smartwatch that utilizes the integration system of the Internet of Things (IoT). A smartwatch is a smart device that functions not only as a conventional timekeeper but also possesses various advanced features such as message notifications, health monitoring, activity tracking, and wireless connectivity with smartphones. This study aims to analyze the development of smartwatch technology, its primary features, and its impact on the efficiency of daily life activities.   The research method used is a literature study with a qualitative descriptive approach, namely by collecting data from relevant journals, books, and scientific articles. The results indicate that smartwatches are developing rapidly alongside technological advancements such as IoT and Artificial Intelligence (AI). These devices provide numerous tangible benefits, particularly in aspects of self-health monitoring, seamless communication, and optimization of user productivity. However, on the other hand, the implementation of this technology also brings negative impacts such as an increase in electronic waste (e-waste), high battery energy consumption, as well as the risk of technology dependency and data privacy vulnerability issues. In conclusion, IoT-based smartwatches represent a technology that contributes significantly to the modern lifestyle ecosystem. Therefore, their utilization needs to be carried out wisely through an increased understanding of data privacy security risks as well as device screen time management so that the benefits obtained can be more optimal and sustainable.